Beginning Teaching - Schuck, Sandy. author. aut Link
XII, 152 p.
Keywords: The experiences of the first years of new teachers’ professional lives are critical to their decisions about embracing or leaving the teaching profession. Writ large, these experiences have the potential to either underpin or undermine the growth and development of the teaching profession. This book offers a research-based account of beginning teachers’ experiences, told from their own perspectives and often in their own words. Beginning Teaching: Stories from the Classroom provides valuable source material to inform teacher education practices. The authors draw on more than 20 years of research on the professional learning, retention and attrition of beginning teachers to provide evocative illustrations of the challenges and successes that occur in the early years of teaching. The compelling and coherent narratives will appeal not only to student and graduate teachers but also to program designers, coaches and senior managers in schools. Above all, the book speaks to teacher educators in the hope that the experiences discussed here will suggest ways of supporting student teachers to grow and flourish once they launch their careers in the profession. These evocative stories express beginning teachers’ anguish and elation and also provide testimony to their resilience and perseverance in an altruistic profession. The analysis and interpretation of their stories will challenge and uplift; inspire and shame; give cause for celebration and melancholy; generate empathy and provoke introspection. Above all else, these stories call for change.